Manejo y utilidad de los recursos didácticos en la enseñanza, aprendizaje de estudios sociales de los octavos año de educación básica de los colegios Dra Matilde Hidalgo de Procel y técnico Une del cantón Machala periodo lectivo 2012-2013 - Luzuriaga Cuenca, Josefina Ángela (2013)
The current curriculum reform considers the use of teaching resources are enablers of holistic learning, so every educational institution should use based on their academic reality and the environment, so the teachers in each area should use teaching resources in classes in order to strengthen and define the content.